Hypoactive Sexual Desire Disorder among women in the climacteric period in clinical practice - Czyżkowska, Anna; Rawińska, Marta; Lew-Starowicz, Zbigniew (Menopause Review/Przegląd Menopauzalny, 2011)
Typical sexual disorders among women in the perimenopausal period include loss of sexual interest, sexual arousal disorders, loss of sexual reaction, orgasm disorders and pain during intercourse. One of the most frequent sexual disorders among women in the climacteric period is hypoactive sexual desire disorder. Pathophysiology of sexual desire disorders has three major dimensions: biologic, motivational, and cognitive. This paper describes also the paradigm that facilitates the diagnosis and treatment of HSDD in the health practitioner’s practice.